Outperformance small cap akcií - Šedivý, Martin; Fičura, Milan; Vyletelka, Michal; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
This bachelor thesis investigates the size factor, introduced by Fama and French (1992), focusing on the outperformance of small-cap stocks. Using historical performance data and linear regression analysis, the study identifies key variables influencing the size factor. In the short term, the size factor exhibits momentum from market and size returns. However, in the long term, market returns tend to have a negative effect. Conversely, rising inflation and credit spreads positively affect the size factor over longer periods. The returns of the size factor has diminished in recent decades, however current environment suggests potential for outperformance of the size factor.
Vedoucí práce: Milan Fičura
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses